Antimicrobial Peptides - William M. Shafer (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
Antimicrobial peptides (AMPs) are gene-encoded, ancient (and important) mediators of innate host defense that exert direct or indirect antimicrobial action as well as possessing other important biologic activities (e.g., neutralization of endotoxin and anti-biofilm action) that help to protect vertebrates, invertebrates and plants from invading pathogens. While the emergence of multi-antibiotic resistant pathogens (and the desperate need to develop new anti-infectives) has been a recent force driving the field, interest in AMPs has an earlier origin in studies of how phagocytes kill bacteria by oxygen-independent processes. AMPs responsible for such killing of microbes by rabbit and human neutrophils were later purified by Ganz, Selsted and Lehrer, which they termed defensins; at the time of this writing, literally thousands of defensin-based publications can be found in the scientific literature! The initial reports on defensins and the earlier report by Boman's group on the purification and action of an insect AMP represented a historical and defining point for the AMP field as they, in hindsight, demanded the recognition of AMP research as a unique discipline that has important linkages to other important fields of medicine, especially those of microbiology, infectious diseases and immunology. On a personal note, I remember conferences on phagocytes and host defense in the early 1980s where the topic of AMPs was relegated to one short session in a five day period! Now, we have hundreds of international "AMPologists" with expertise in chemistry, biochemistry, molecular and structural biology, cell biology, microbiology, pharmacology, or medicine who have built their research careers around AMPs and can now attend international conferences dedicated to advances in AMP research.